Correlação entre intensidade da dor, desempenho funcional e capacidade física em idosos com dor lombar agudizada: dados do estudo Bace Brasil - Amanda Aparecida Oliveira Leopoldino (2013)
Population ageing is a reality and pain prevalence among elderly people is high, altering functional performance and physical capacity causing negative impact on their quality of life, this way, studies about back pain impact on elderly functionality must be encouraged. In this context, functional tests with clinical applicability that contemplate the categories exposed by the International Classification of Functioning, Disability and Health (ICF) and data from self-related instruments of pain and physical function are widely used. Therefore, the objective of this study was to verify if there is correlation between pain intensity measured by Numerical Pain Scale (NPS) and pain related to functional performance by the pain domain of Western Ontario and McMaster Universities (WOMAC) Osteoarthritis Index, between pain and physical capacity assessed by the Timed up and go (TUG) and gait speed test and between these two functional tests and Womac´s physical function domain in community-dwelling elderly with acute low back pain. This is a cross-sectional study, derived from an international consort - Back Complaints in the Elderly (BACE), among Brazil, Australia and the Netherlands. Subjects included in the study must be 60 years or older, have a new episode (crisis/reagudization) of low back pain in the last six weeks and those with cognitive impairment detectable by the Mini-Mental State Examination were excluded. Data analysis was conducted using Spearman´s Correlation Coefficient (r) for all outcome variables at a significance level of = 0.05. The sample was composed by 225 elderly with mean age of 68.1 (± 5.83) and mainly were women (86.7%). The mean score of current END was 4.73 and for the last seven days was 6.85, the mean score of WOMAC´s pain domain was 49.39 and the physical function domain mean score was 44.90. TUG´s mean value was 11.27 seconds and gait speed mean value was 1.01meters/second. Correlations between current END score and 7 days END score were o.53 and 0.45, respectively; correlations between TUG and gait speed and WOMAC´s physical function domain were 0.33 e -0.31, respectively, and correlations between current END and 7 days END and TUG and gait speed were 0.10; 0.23; -0.19 e -0.23, respectively. Our results showed relevant clinical results about pain and performance and physical capacity level of community-dwelling elderly with acute low back pain, allowing Physical Therapists and other health care professionals to better understand these outcomes and in this way, develop more assertive strategies to approach elder individuals with back pain.